Peningkatan Hasil Belajar Matematika Melalui Pembelajaran Matematika Realistik pada Siswa Kelas VI SD Negeri 40 Muaro Takung Kecamatan Kamang Baru Kabupaten Sijunjung - Fitri Yanse (Warta Pendidikan | e-Journal, 2020)
Learning will be meaningful if the teacher involves students directly in learning. The results of observations show that the teacher has not directly involved students in learning so that the mathematics learning outcomes are still low. This study aims to improve Mathematics learning outcomes through Realistic Mathematics Learning in grade VI SD Negeri 40 Muaro Takung, Kamang Baru District, Kab. Sijunjung Learning outcomes used include cognitive learning outcomes and student attitudes while participating in learning. This research is a classroom action research conducted collaboratively with class teachers. The research design used a modified Kemmis & McTaggart model in 2 cycles consisting of planning, implementing, observing, and reflecting. The subjects of the study included 15 grade students of SD Negeri 40 Muaro Takung. The object of research is the result of learning mathematics through realistic mathematics learning. Data collection techniques are tests and observations. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the mathematics learning outcomes of grade VI students at SD Negeri 40 Muaro Takung, Kamang Baru District, Sijunjung Regency could increase after being given action through Realistic Mathematics Learning. Realistic Mathematics Learning used is to use real problems in life, use props, discuss results, find concepts, then the teacher introduces standard procedures / formulas and links other concepts in related mathematics. Students do not immediately get the formula but first the students are directly involved in making observations using props and group discussions so that they find a concept. Cognitive learning outcomes in pre-action showed that as many as 6 students (20%) had reached the KKM then in cycle I increased to 17 students (53.33%) and in cycle II increased to 27 students (80%). The average result of the attitude in the first cycle reached 58.33% while the second cycle the attitudes average was 77.5%. Thus, Realistic Mathematics Learning can improve the mathematics learning outcomes of Grade VI students of SD Negeri 40 Muaro Takung, Kamang Baru District, Sijunjung Regency.